2011
DOI: 10.1111/j.1365-4632.2011.04875.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologists’ level of compliance with the prescription guidelines of isotretinoin for females of childbearing potential

Abstract: Some dermatologists still do not follow the recommendations for isotretinoin prescription to FCBP. This needs to be corrected, especially in countries with restrictions on abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
(22 reference statements)
3
7
0
Order By: Relevance
“…A recent survey conducted among dermatologists in Saudi Arabia [25] showed also that some dermatologists are not compliant with recommendations for isotretinoin use in women of childbearing potential. This study is one of the few studies performed among dermatologists and the actual adherence to the PPP.…”
Section: Expert Opinionmentioning
confidence: 99%
“…A recent survey conducted among dermatologists in Saudi Arabia [25] showed also that some dermatologists are not compliant with recommendations for isotretinoin use in women of childbearing potential. This study is one of the few studies performed among dermatologists and the actual adherence to the PPP.…”
Section: Expert Opinionmentioning
confidence: 99%
“…They did not provide them with adequate information about the teratogenic effect of isotretinoin. 11 Instead, certain papers revealed that the pharmacist educated the patients properly and provided them with sufficient knowledge to recognize the risks associated with their medication by using specific programs such as iPLEDGE. [12][13][14] There is a gap between the proven efficacy of isotretinoin capsules that are prescribed by a dermatologist in the clinic and their actual effectiveness in practice.…”
Section: Introductionmentioning
confidence: 99%
“…It carries many unfavorable side effects such as teratogenicity, abnormal lipid profile, psychiatric issues, and dryness, which is the most common complaint among users [7]. Due to its teratogenicity, females of childbearing age must be advised to be on two or more contraception methods while on treatment [8]. In addition, regular monitoring and patient follow-up are recommended.…”
Section: Introductionmentioning
confidence: 99%